Effects of the great recession on drugs consumption in Spain - Martín Bassols, Nicolau; Vall Castelló, Judit (Economics and human biology, 2016)
This paper presents evidence on how the consumption of legal and illegal drugs has changed in response to the Great Recession in Spain. We use a large scale survey from 2005 to 2011 to analyze the association between changes in local economic conditions and drug consumption among individuals aged 15-64. Although Spain was one of the countries hardest hit by the economic downturn, the crisis was unevenly felt across the country. Therefore, we exploit this difference in unemployment rates across provinces to identify the effects of business cycle variations on the consumption of legal and illegal drugs. To the best of our knowledge, this is the first study to find a relation between the deterioration of local economic conditions and a strong increase in the consumption of marihuana and cocaine. We also report a decrease in alcohol consumption but a significant escalation in abusive smoking behavior (smoking every day). We believe that these findings are important not only for the potential negative implications at the individual level but also for the costs to society as a whole.
Gesehen am 22.04.2020